Simulation of the calcination of a core-in-shell CuO/CaCO 3 particle for Ca–Cu chemical looping - Qin, Changlei; Manovic, Vasilije; Ran, Jingyu; Feng, Bo (Elsevier, 2016)
The internal heat balance through heat generation due to CuO reduction and its consumption by CaCO3 decomposition makes calcination a critical step in a novel Ca–Cu chemical looping process (CaL–CLC). Thus, the calcination behaviour of composite Ca/Cu particles needs to be well understood, especially taking into account that mismatching of heat generation and consumption in the particles can lead to local superheating, agglomeration and loss of activity due to enhanced sintering. In this work, a composite particle model was developed to study the calcination behaviour within a spherical core-in-shell type of particle containing grains of CuO and CaCO3. Simulation results showed that ambient temperature, shell porosity, particle size, and CaCO3 grain size significantly affected the CuO and CaCO3 reaction processes, while the impact of initial particle temperature and CuO grain size can be ignored in the range of parameters considered in the study. By comparison of different types of particles, it was concluded that the core-in-shell pattern was more advantageous if such particles are being applied in CaL–CLC cycles due to better matching in reaction kinetics resulting in more stable and uniform particle temperature distribution during the calcination stage.
Keywords: Ca–Cu chemical looping; CO2 capture; Core-in-shell particle; Composite particle model